Stressing the 'body electric': History and psychology of the techno-ecologies of work stress. (December 2022) - Pykett, Jessica; Paterson, Mark
This article explores histories of the science of stress and its measurement from the mid 19th century, and brings these into dialogue with critical sociological analysis of emerging responses to work stress in policy and practice. In particular, it shows how the contemporary development of biomedical and consumer devices for stress self-monitoring is based on selectively rediscovering the biological determinants and biomarkers of stress, human functioning in terms of evolutionary ecology, and the physical health impacts of stress. It considers how the placement of the individual body and its environment within particular spatio-temporal configurations renders it subject to experimental investigation through standardized apparatus, electricity, and statistical normalization. Examining key themes and processes such as homeostasis, metricization, datafication, and emotional governance, we conclude that the figure of the 'body electric' plays a central limiting role in current technology-supported approaches to managing work stress, and that an historical account can usefully open these to collective scrutiny.